DISSEMINATED INTRAVASCULAR COAGULATION - Naz, Humaira; Fawad, Anisa; Islam, Ansa; Shahid, Hamna; Abbasi, Aziz -un-Nisa (Journal of Ayub Medical College Abbottabad, 2011)
Background: Disseminated Intravascular Coagulation (DIC) is a complex systemic thrombohaemorrhagic disorder characterised by widespread endothelial damage. Aim of this study was to assess the prevalence of DIC in different obstetrical conditions. Methods: This descriptive study was carried out in the Department of Obstetrics and Gynaecology Unit '˜A', Ayub Medical College, Abbottabad from January 2010 to December 2011. All 40 diagnosed cases of DIC were included, and their risk factors and maternal/foetal outcome were evaluated. Results: Out of 4,334 obstetrical admissions, DIC was diagnosed in 40 (0.92%) patients. Risk factors noted were eclampsia 28 (70%), abruptio placentae 7 (17.5%), septicaemia 3 (7.5%), pancytopenia 1 (2.5%), and 1 (2.5%) patient had DIC secondary to haemorrhagic shock due to placenta previa. Mean age range of patients was 31±6.69 (19-48) year, and parity was 3.17±2.56 (0-10). Mode of delivery of 34 (85%) patients was by caesarean section, and vaginal delivery occurred in 3 (7.5%) patients. Eleven (27.5%) patients had caesarean hysterectomy. Maternal mortality was 25% and perinatal mortality was (47.5%). Majority of our patients were critical and were managed in ICU. Conclusion: DIC is serious life threatening condition secondary to any underlying pathology. There is spontaneous resolution of DIC after correction of pathology. Keywords: DIC, Eclampsia, Abruptio placentae, placenta previa, haemorrhagic shock